BIO-EFFICACY OF SOME NEWER INSECTICIDES AGAINST WHITEFLY, BEMISIA TABACI (GENNADIUS) AND THRIPS, SCIRTOTHRIPS DORSALIS (HOOD) INFESTING BT COTTON - SUVASH CH. BALA; NIHAL R. (The Bioscan, 2020)
Field experiments were conducted at the District Seed Farm (A B - Block farm), Kalyani, Nadia, West Bengal during rabi season 2016-2017 and 2017-18 to evaluate the effectiveness some newer insecticides developed by different companies against cotton Whitefly and Thrips. Experiments were laid out in randomized block design (RBD) with nine treatments and three replications. The experimental data revealed that The treatment Diafenthiuron+ Acetamiprid in three different doses viz. 400, 500, 600g/ha was effective in suppressing whitefly population. The highest mortality (83.05%) of whitefly population was noticed from the treatment Diafenthiuron+ Acetamiprid @ 600g/ha which is statistically at par with Diafenthiuron+ Acetamiprid @ 500g/ha (81.89%) after 3 days of spraying. For the management of thrips, the treatment Diafenthiuron+ Acetamiprid @ 600g/ha and Diafenthiuron+ Acetamiprid @ 500g/ha was registered maximum thrips mortality of 72.01 % and 67.97 % respectively. From the study it was inferred that the combined insecticide Diafenthuron+ Acetamiprid @ 600g/ ha was most effective in controlling the sucking pests such as Whitefly and thrips in cotton.